Custom Dual Impression Tray Technique: A Case Report on Management of Flabby Maxillary Ridge - Kansakar, Kerishna; Dhital, Shaishav; Ghimire , Barsha (Journal of Nepalese Prosthodontic Society, 2025)
With an increased prevalence of edentulousness, dentists can encounter individuals who are partially edentulous in the mandible and completely edentulous in the maxilla. This clinical scenario commonly presents with flabby tissue in the maxillary ridge. Flabby tissue is challenging to manage as this affects the stability and retention of the prosthesis. Such cases can be managed by surgical approach, by use of implants or by conventional method where we use various impression techniques to carefully capture the flabby tissue. This case report describes the use of customized dual impression tray based on the modification of Osborne’s technique which was developed by Devlin to manage flabby maxillary ridge in a patient.